Enhancing the durability of Ti–Al–C coatings: The role of powder composition and processing variables - Huanhuan Hong; Panpan Yang; Xiang Gui; Yang Yang; Xia Liu; Jianxiang Ding; Gobinda Gyawali; Kang Yang; Shihong Zhang (Journal of Materials Research and Technology)
This study investigated the influence of aggregate powder compositions (Ti–Al-Graphite/Ti–Al–TiC) and processing variables on microstructure, phase composition, and tribological properties of atmospheric plasma sprayed Ti–Al–C coatings. The coatings exhibited a distinct layered structure, with variations in phase composition and microstructure attributed to differences in agglomerated powder and spraying conditions. Incorporating TiC in the agglomerated powder significantly improved the hardness and bonding strength of the coatings. High-temperature friction and wear tests demonstrated superior wear resistance of the TiC-containing coatings compared to those with graphite. The formation of a protective oxide layer, consisting of TixAly and Ti2AlC phases, during frictional sintering oxidation led to enhanced wear resistance at elevated temperatures. The mechanisms of friction and wear in these coatings involved oxidative wear, adhesive wear, and fatigue wear. The results suggest that the composition of the Ti–Al–C coatings can be tailored to optimize their high-temperature tribological performance for various applications.